An Unusual Pattern of Closed Flexor Tendon Avulsion - Ching, Rosanna C.; Stevenson, Susan (Journal of Hand and Microsurgery, 2019)
Closed avulsion of both flexor tendons is an uncommon injury pattern. We discuss a classic rugby jersey injury that resulted in avulsion of both flexor tendons with the flexor digitorum superficialis (FDS) avulsion incorporating a large fracture of the middle phalanx. To our knowledge, this pattern has been described only once in the literature. We propose a modification to the flexor tendon avulsion classification allowing incorporation of this injury pattern to help guide its management.
Keywords: flexor tendon; avulsion; fracture; jersey finger